Composite Materials: Robotic Tentacles with Three‐Dimensional Mobility Based on Flexible Elastomers (Adv. Mater. 2/2013). (7th January 2013) - Martinez, Ramses V.; Branch, Jamie L.; Fish, Carina R.; Jin, Lihua; Shepherd, Robert F.; Nunes, Rui M. D.; Suo, Zhigang; Whitesides, George M.
<x xml:space="preserve">Abstract</x> The front cover image illustrates a soft robotic tentacle with a textured surface fabricated by composing flexible elastomers using soft lithographic molding. These soft tentacles can manipulate delicate objects and house functional components that extend their capabilities (for example, a video camera). More details can be found in the article by George M. Whitesides and co‐workers on page 205. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>